The Ehub Modeling Tool: A flexible software package for district energy system optimization. (September 2017) - Bollinger, L. Andrew; Dorer, Viktor
Abstract: Effective planning and control of district energy systems must account for numerous complexities and uncertainties, requiring advanced computational tools. This paper introduces the Ehub Modeling Tool, an open source software package for preliminary design optimization of district energy systems. Using automated code generation techniques that directly translate raw data descriptions of a given district into executable optimization code, the tool simplifies and accelerates the process of developing and executing district energy system optimizations, and visualizing/interpreting results. Example applications of the tool in research and education are described.